Analisis Kebijakan Sertifikasi Guru dalam Meningkatkan Mutu Pendidikan di SMPN 47 Surabaya - Herdianti, Nadira Ferisa; Awaliyah, Nabilah Putri; Listari, Nabilah Dwi; Trihantoyo, Syunu; Nuphanudin, Nuphanudin (Lembaga Yasin AlSys, 2024)
This study examines the effectiveness of the teacher certification policy aimed at improving educational standards at SMP Negeri 47 in Surabaya, with a focus on how it affects teacher’s competence, welfare, and skills. The certification policy is hypothesized to play a pivotal role in elevating the quality of education offered. Employing a qualitative approach, this study examines the implementation and outcomes of the policy since its introduction. Data was collected through various qualitative methodologies and analyzed to ascertain the policy’s contribution to enhancing teacher welfare, competence, and professionalism. The findings reveal that the teacher certification policy at SMPN 47 Surabaya has been significantly instrumental in advancing educational quality aligning with the policy’s prime objectives. These insights hold wide implications for educational policy optimization at a broader level.